2020
DOI: 10.1101/2020.11.24.396051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Primeval Mechanism of Tolerance to Desiccation Based on Glycolic Acid Saves Neurons from Ischemia in Mammals by Reducing Intracellular Calcium-Mediated Excitotoxicity

Abstract: Stroke is the second leading cause of death and disability worldwide. Current treatments, like pharmacological thrombolysis or mechanical thrombectomy, re-open occluded arteries but do not protect against ischemia-induced damage caused before reperfusion or ischemia/reperfusion-induced neuronal damage. It has been shown that knocking out djr-1.1 and djr-1.2 or glod-4 results in a decreased tolerance to anhydrobiosis in C elegans dauer larva and that Glycolic Acid (GA) can rescue this phenotype. During the proc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Despite the inability to regulate this genes, our results show that high concentrations of GA and DL still have neuroprotective properties in mammals. In a recently published study, we showed that GA protects against ischemia in several stroke models: in an oxygen glucose deprivation (OGD) model in vitro , in a global cerebral ischemia mouse model and in a middle cerebral artery occlusion mouse model 34 . We have also been able to reproduce the in vitro results in dopaminergic neurons in a mouse model of PD generated by exposing WT and DJ-1 KO mice to PQ.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the inability to regulate this genes, our results show that high concentrations of GA and DL still have neuroprotective properties in mammals. In a recently published study, we showed that GA protects against ischemia in several stroke models: in an oxygen glucose deprivation (OGD) model in vitro , in a global cerebral ischemia mouse model and in a middle cerebral artery occlusion mouse model 34 . We have also been able to reproduce the in vitro results in dopaminergic neurons in a mouse model of PD generated by exposing WT and DJ-1 KO mice to PQ.…”
Section: Discussionmentioning
confidence: 99%